O uso do podcast como ferramenta para o ensino de física - Lizarazu, Eduardo Silveira Dantas (2019)
Bearing in mind that technology has being increasingly used in education, the present work aims to promote the use of the podcast as a tool for Physics teaching. The podcast is a way to share content, predominantly audio, using a series of episodes that the user can download to his phone or other devices of personal use. These podcasts are usually made available through websites, blogs and applications on the internet. This dissertation presents a methodology for the process of developing podcasts for Teaching Physics in a collaborative way including students and teachers. During this process, a sequence of activities was carried out with a group of students, in which they were carried out as stages of planning, production and publication of podcasts on mechanics and thermal physics. In addition to elaborating the methodology, we sought to verify whether it proves to be viable and with the potential for alternative teaching of Physics, through the analysis of students' performance after the production of podcasts. The present work also discusses the potential and limitations of this tool for teaching Physics. The educational product present in this work consists of a booklet with a complete tutorial for teachers with and without experience in the production of podcasts, focusing on the production in a collaborative way with their students, and in podcasts aimed at teaching Physics in High School, especially detailing the stages of planning, preparing and publishing these podcasts.